Employment Guarantee Scheme in Maharashtra A Preliminary Observation - Planning Commission (Planning Commission, 1993)
"Under a Resolution (March 28, 1972), the Government of Maharashtra sanctioned the Employment Guarantee Scheme (EGS) which received the Statutory support through an enactment of Maharashtra Employment Guarantee Act, 1977. The work under the Scheme had started from May, 1972. The Scheme is intended to provide gainful and productive employment in approved works to all adult unskilled persons residing in rural areas and in 'C' class municipal councils. 2. Under another Resolution, Shram Shakti Dware Gram Vikas was formulated in June, 1989 with a view to taking up the development works in a village in an integrated manner."
"Programme Evaluation Organisation Planning Commission (Government Of India) New Delhi"